SOIL FERTILITY IDENTIFICATION OF PADDY FIELD ON LAND USE AGE VARIOUS INKERANJI PAIDANG VILLAGESENGAH TEMILA SUB-DISTRICTLANDAK DISTRICT - Suherman Suherman, Rini Hazriani, Abdul Mujib Alhaddad (Jurnal Sains Pertanian Equator, 2019)
Soil fertility is the capablelity of a soil to provide nutrients at certain doses in equilibrium continuously to support the growth of a type of plant in the environment with other growth factors in favorable conditions.The objectives in this study were to determine the nutrient status of Nitrogen (N), phospor (P), Potassium (K), soil reaction (pH), C-organic, cation exchange capacity (CEC), and base saturation (BS) on rice fields in Keranji Paidang Village. For providing recommendation on plant fertilization on site specifics on rice fields in Keranji Paidang Village.This research was carried out on rice fields in Keranji Paidang Village Sengah Temila Sub-district Landak District by methode of land survey and soil analist. The area of rice fields studied is ± 2.56 ha. The materials used are soil samples and chemicals. The tools used in the field are: meter, ground drill, knife, plastic bag, documentation tool, label paper, stationery, supporting maps and GPS.          The results of the study, based on the results of analysis of soil reactions (pH) at the 6-year (P1), 25-year (P2), and 12-year (P3) study sites were classified as acidic between 4.70, 4.56, and 4.52, whereas at the location of 20 years (P4) it is classified as very acidic which is 4.47. Very high C-organic content is found in locations P1 and P2, which are 10.28% and 13.97%. The location of P3 is relatively high at 4.28% and at location P4 is classified as moderate, which is 2.60%. Nutrient N at the research location P1 and P2 was classified as very high at 0.96 and 1.26%. The location of P3 is classified as high, namely 0.53% and P4 is classified as moderate, which is 0.32%. Each research location has a total P land content and P is very high available land and low K-total soil content and very low available K land. Cation exchange capacity at locations P1 and P2 is high and very high at 34.71 and 42.51. P3 and P4 locations are low, namely 13.59 and 9.85. Very low KB values were found in P2 and P1 locations, namely 8.80% and 10.80%, and low KB values were 22.74% and 22.96% in locations P4 and P3.          Based on the results of the analysis and comparison of soil fertility levels, it can be concluded that the study sites have the same fertility level criteria but there are different nutrients.Key words: soil fertility, rice fields, land use age.